O impacto de novas tecnologias de informação no processo de criação publicitária - Mello, Fábio Luiz Jardim (2007)
The present work discusses on how new information technologies privilege and make the use of file/archive images easy within the marketing creative process today. This study aims at digital image data as well as understanding how they have come up, developed and currently impacted on the marketing creative process. Moreover, how the new information technologies - such as the digital photograph and the data transmission/or transfer/or boadcasting within the ciberspace - have made easy the access to such an image acquisition resource. The research is firstly founded on a theoretical discussion basis, where a reflexion on the steadfast human being seek for the accelaration of production, transport, information and experience means was then developed. In this first theoretically based section, we are making use out of Socio-dromology concepts in order to deeply understand both the relations between speed and violence, as well as those between existence haste and dominance. Next, a research on the advent of some companies skilled at first gathering photograph lots and eventually disposing the right to use them for marketing or publishing communication interests is presented. The Semiotics theories on photograph have helped us better understand the image cult value and its prolificacy in the media visibility. Secondly, setting out in search, a discussion on the relation between data basis and marketing creation was developed. Such information was collected by interviewing the most important operating image date basis directors and founders within this worldwide market, in which every piece of information was analysed as of the peircean-lined and semiotics-based creative process studies